Distiller’s Dried Grains With Solubles (DDGS) for Animal Feed - Budi Tangendjaja (Indonesian Center for Animal Research and Development, 2008)
Distiller’s Dried Grains with Solubles (DDGS) is co-product from dry milling of ethanol industry after removal of ethanol and CO2. From every 25.4 kg (1 bushel) of corn, it can produce around 7.7 kg of DDGS. DDGS offers an opportunity for cost savings in animal feed rations, and will be available in abundant quantities in coming years. DDGS has been traded in many parts of the world with 27% protein, 9 – 10% fat and < 7% fiber. Although DDGS is mainly used for feeding ruminant, more DDGS are used for monogastric animals such as swine and poultry and recently an interest to be used for aquaculture. Recent studies by University of Arkansas indicated that Metabolizable Energy value of DDGS for poultry is 2850 kcal/kg. It was also reported that DDGS can be included up to 15% in broiler feed without affecting performance and higher level of inclusion was possible for finisher broiler. On swine diet, Digestible and Metabolizable Energy of DDGS is equal to corn and much higher value than that reported by NRC 1998. DDGS is a good source of protein, fat, phosphorus and energy for lactating dairy cows. Distiller’s grains can be included in dairy cow diets up to 20% of the ration without decreasing dry matter intake, milk production, milk fat and protein percentage. For beef cattle, it can effectively be used as an energy source and be fed up to 40% of ration with excellent growth performance, carcass and meat quality. For aquaculture, DDGS can be used up to 30% in freshwater fish such as catfish and tilapia and up to 20% in trout; it can also be used to feed shrimp up to 10%. However, in order to use DDGS for animal feeding, several quality factors include physical, chemical and biological should be considered especially in formulating a diet. DDGS quality may vary depending on the origin and corn quality, processing condition especially drying temperature and time and amount of solubles being added to distiller’s grains. Key words: DDGS, feed, protein, energy